Recent Gene Therapy Advancements for Neurological Diseases - Kalburgi, Sahana Nagabhushan (Discov Med, 2013)
The past few years have seen rapid advancements in vector-mediated gene transfer to the nervous system and modest successes in human gene therapy trials. The purpose of this review is to describe commonly-used viral gene transfer vectors and recent advancements towards producing meaningful gene-based treatments for central nervous system (CNS) disorders. Gene therapy trials for Canavan disease, Batten disease, adrenoleukodystrophy, and Parkinson’s disease are discussed to illustrate the current state of clinical gene transfer to the CNS. Preclinical studies are under way for a number of diseases, primarily lysosomal storage disorders, using a newer generation of vectors and delivery strategies. Relevant studies in animal models are highlighted for Mucopolysaccharidosis IIB and Krabbe disease to provide a prelude for what can be expected in the coming years for human gene transfer trials, using recent advancements in gene transfer technology. In conclusion, recent improvements in CNS gene transfer technology are expected to significantly increase the degree of disease rescue in future CNS-directed clinical trials, exceeding the modest clinical successes that have been observed so far.